If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = y + -2x Reorder the terms: 6 = -2x + y Solving 6 = -2x + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 6 + 2x = -2x + 2x + y Combine like terms: -2x + 2x = 0 6 + 2x = 0 + y 6 + 2x = y Add '-6' to each side of the equation. 6 + -6 + 2x = -6 + y Combine like terms: 6 + -6 = 0 0 + 2x = -6 + y 2x = -6 + y Divide each side by '2'. x = -3 + 0.5y Simplifying x = -3 + 0.5y
| 3+7=40 | | 5x+5(x-6)=5(x-5) | | 6+3=36 | | 8x+8y=240 | | .33333x-21=33 | | 3x+12=2x+6 | | t*2+4t*2= | | 3h+28=82 | | 6+3=56 | | 4(2x)+4(3x)= | | 14+5x=(-x+3)-11 | | -13x+16=10 | | 2x-25+3x+x+6+4x-11=360 | | -4x-2(8x+1)=-2x-10 | | 4+3=56 | | 5(x+3)-5=2x+1 | | -2x-25+3x+x+6+4x-11=360 | | -2x^2-6x-9=0 | | 6-6=3x | | 12.7(x+11)=61.6 | | y+10.24=5.3 | | 3b-7=8 | | 4c-2c+3=17 | | 2p+6b=675 | | -2-25+3x+x+6+4x-11=360 | | 12+-14= | | -6(v+2)+4v+5=7v+12 | | -2x-59=21-7x | | 1+x-x^2-x^4=0 | | 9(r-8)= | | 2(3x-8)-4=10 | | 12x=126 |